2015
DOI: 10.1038/jcbfm.2015.33
|View full text |Cite
|
Sign up to set email alerts
|

Combined Ampakine and BDNF Treatments Enhance Poststroke Functional Recovery in Aged Mice via AKT-CREB Signaling

Abstract: Cerebral ischemia results in damage to neuronal circuits and lasting impairment in function. We have previously reported that stimulation of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors with the ampakine, CX1837, increases brainderived neurotrophic factor (BDNF) levels and affords significant motor recovery after stroke in young mice. Here, we investigated whether administration of CX1837 in aged (24 months old) mice was equally effective. In a model of focal ischemia, administration of CX183… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 41 publications
(97 reference statements)
4
57
0
Order By: Relevance
“…Neurological outcome and axonal regeneration are tightly regulated by many extracellular factors [1]. Neurotrophins including brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF) and neurotrophin-3 (NT3) promote neuronal survival and synaptic plasticity, whereas the nogo receptor and its ligands restrict the process [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Neurological outcome and axonal regeneration are tightly regulated by many extracellular factors [1]. Neurotrophins including brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF) and neurotrophin-3 (NT3) promote neuronal survival and synaptic plasticity, whereas the nogo receptor and its ligands restrict the process [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have shown the efficacy of BDNF in improving post-stroke recovery in animal models (Clarkson et al., 2015; Yu et al, 2013), BDNF was given quite quickly after stroke onset, a therapeutic time-window that is often not practical in clinical situations. In this study, extended therapeutic windows were evaluated, with treatment delayed for over 12 hours after stroke onset.…”
Section: Discussionmentioning
confidence: 99%
“…Although BDNF expression is upregulated after stroke injury this effect is transient and is reduced with age, making plasticity-based recovery paradigms difficult in chronic stroke and aged populations. While systemically delivered AMPAkine stimulated recovery in young animals, by inducing BDNF release (Clarkson et al, 2011), recovery was dampened in aged animals (Clarkson et al, 2015) due to reduced BDNF expression in this population. Interestingly, combining the systemically administered AMPAkine with local BDNF delivery through a HA-based hydrogel modified with collagen-binding domains improved recovery in aged animals to levels comparable to young animals (Clarkson et al, 2015).…”
Section: Promoting Plasticitymentioning
confidence: 99%
“…While systemically delivered AMPAkine stimulated recovery in young animals, by inducing BDNF release (Clarkson et al, 2011), recovery was dampened in aged animals (Clarkson et al, 2015) due to reduced BDNF expression in this population. Interestingly, combining the systemically administered AMPAkine with local BDNF delivery through a HA-based hydrogel modified with collagen-binding domains improved recovery in aged animals to levels comparable to young animals (Clarkson et al, 2015). This is one of the few studies involving biomaterials that investigated mechanistic pathways mediating this process, demonstrating that BDNF delivered from the hydrogel upregulates canonical BDNF signaling pathways.…”
Section: Promoting Plasticitymentioning
confidence: 99%
See 1 more Smart Citation